Pengaruh Kualitas Pelayan Unit Informasi Terhadap Kepuasan Penumpang di PT. Angkasa Transportindo Selaras (ATS) Bandar Udara Internasional Halim Perdanakusuma Jakarta - Alfriend Juang Waruwu; Nanik Rianandita Sari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
One of the important units in airport operations is the information unit which has a very important role in supporting airport operational activities. According to the author's research, Halim Perdanakusuma Airport's information unit service is still thought to not offer the best possible care, which lowers customer satisfaction. In this study, the impact of information unit service quality on passenger satisfaction at Jakarta's Halim Perdanakusuma International Airport is to be investigated. This research uses quantitative research methods using data collection techniques obtained directly by distributing questionnaires online which are distributed to passengers, through research documentation and observation. This study's findings support the author's hypothesis that there is a positive and significant relationship between information unit X's service quality and passenger Y's satisfaction, indicating that Ho is rejected and Ha is accepted. This is supported by the calculated t value for information unit service quality, which is 15.740 > 1.66. Additionally, the coefficient of determination (R²) was determined to be 0.723, or 72.3%, of the total, with the remaining 27.7% being influenced by factors not covered in the study